2014
DOI: 10.1074/jbc.m114.559583
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hyaluronan Synthesis Protects against Central Nervous System (CNS) Autoimmunity and Increases CXCL12 Expression in the Inflamed CNS

Abstract: Background: Hyaluronan accumulates in chronic demyelinated multiple sclerosis (MS) lesions. Results: 4-Methylumbelliferone (4MU) inhibits HA synthesis, is protective in active and passive MS models, modulates T-cell responses, and prevents CXCL12 suppression within inflamed and non-inflamed CNS tissue. Conclusion: Inhibition of hyaluronan synthesis protects against CNS inflammation. Significance: Study data substantiate a link between hyaluronan and CNS inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
4
45
1
Order By: Relevance
“…This is consistent with our recent report of 4-MU-mediated enhancement of Treg in mouse models of autoimmune diabetes (27) and with past work on the impact of 4-MU on EAE (22). Our data indicate that 4-MU also promotes increased expression of GITR, a key effector molecule for Treg (23,24).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is consistent with our recent report of 4-MU-mediated enhancement of Treg in mouse models of autoimmune diabetes (27) and with past work on the impact of 4-MU on EAE (22). Our data indicate that 4-MU also promotes increased expression of GITR, a key effector molecule for Treg (23,24).…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we have examined the impact of 4-MU, an inhibitor of HA synthesis, on disease progression in the murine EAE model of MS. We demonstrate that 4-MU can both prevent EAE and ameliorate established disease, corroborating earlier findings (22). Moreover, we show that 4-MU treatment alters the phenotypic polarization of T cells and their trafficking to inflamed CNS tissue that underlies disease progression in this model.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…One study reported that 4-MU treatment reduced MMP expression in a mouse model of collagen-induced arthritis (42). Another recent report suggested that 4-MU increased spinal cord expression of CXCL12 and decreased Th1 responses, while increasing numbers of Tregs (43). Here, we established that HA inhibits FOXP3 expression via a CD44-and ERK1/2-dependent pathway, that 4-MU promotes Treg numbers via increased differentiation, and that these Tregs constrained effector T cells at the site of autoimmunity.…”
Section: Methodsmentioning
confidence: 99%